2012
DOI: 10.3329/jbau.v10i1.12040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of density and flock size on growth performance of native chicken

Abstract: A total of 270 native chickens of two months of age were reared up to their six months of age under three densities .70) FCR value. Body weight gain was found to be the lowest (4.81) in F 3 unit but its FCR and mortality rate were the highest (11.25 and 17.71). Feed intake was observed to be the lowest (49.17) in the F 1 unit. Considering the growth performance of native chickens under different densities and flock sizes, it could be concluded that flock size F 2 (30 birds/flock) performed better at the densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The mortality rate in present study was in accordance with Misba and Aberra (2013) and Ali et al (2012), who observed that the increased rate of mortality with age. The major environmental factors responsible for increased rate of mortality during 9-to 18-weeks of age in present study was the prevalence of disease (coccidiosis).…”
Section: Discussionsupporting
confidence: 92%
“…The mortality rate in present study was in accordance with Misba and Aberra (2013) and Ali et al (2012), who observed that the increased rate of mortality with age. The major environmental factors responsible for increased rate of mortality during 9-to 18-weeks of age in present study was the prevalence of disease (coccidiosis).…”
Section: Discussionsupporting
confidence: 92%
“…ĹžimĹźek and Ă–zhan (2015) reported that there was no difference in final BW of broilers reared in different flock sizes of 15 000, 25 000, and 35 000 chickens. In addition, Ali et al (2012), Rind et al (2004), and TĂĽrkyılmaz (2008 reported that the slaughter BWs of broilers reared in different group sizes were not statistically different. As in our study, the results of relevant studies on the effects of group size on body weights are not always in the same direction and as expected.…”
Section: Discussionmentioning
confidence: 98%
“…In the same research (Toghyani et al, 2010) compared wood shavings litter, rice hulls, paper rollers, sand, and no litter showed no different results in mortality. (Ali et al, 2012) using a stocking density of 0.186; 0.279 and 0.372 m 2 /bird rearing up to 2-6 months did not affect mortality, while this study used a density of 8, 12 and bird/m 2 (0.125; 0.083 and 0.063 m 2 / bird).…”
Section: Mortalitymentioning
confidence: 77%